Strategi Bisnis yang Berkelanjutan Melalui Inovasi dalam Model Operasional di Era Digitalisasi - Septian Bagus Triatmojo; Revangga; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
In the current era of business digitalization, innovation in operational models is very important to maintain the sustainability of business strategies. This research aims to investigate how the application of digital technology can change operational models to support sustainable business strategies. Using a qualitative approach, this research analyzes various case studies of companies that have successfully implemented digital innovation in their operations. This analysis focuses on changes in the value chain, adapting to new technologies, and developing an organization's ability to survive in an unstable environment. The research results show that digitalization helps companies increase efficiency, transparency and responsiveness to sustainability demands from markets and regulations. In addition, this research identifies important factors that influence the success of digital technology integration, such as visionary leadership, a culture of innovation, and organizational readiness to accept change. These findings contribute to the business strategy literature by offering a framework for sustainable operational model innovation in the digital era. Additionally, this study provides practical insights for business stakeholders seeking to ensure sustainability and competitiveness in an ever-changing economy. Managerial implications and recommendations for future research are also discussed in this study.